miR-92b-3p Protects against Myocardial Ischemia-Reperfusion Injury by Inhibiting MAP3K2 in a Mouse Model - Zhao, Kun; Wang, Mei (The Thoracic and Cardiovascular Surgeon, 2024)
MicroRNAs are well-known RNA regulators modulating biological functions in complex signaling networks. This work aims to explore the impact of microRNA-92b-3p (miR-92b-3p) on myocardial ischemia-reperfusion (I/R) injury.The I/R model was established by left anterior descending coronary artery ligation in mice. The hemodynamic parameters were detected through a multichannel physiological recorder. Myocardial injury markers: serum cardiac troponin I, myocardial kinase isoenzyme (creatine kinase-MB), and serum inflammatory factors (tumor necrosis factor-α, interleukin [IL]-1β, and IL-6) were evaluated by enzyme-linked immunosorbent assay. Cardiac tissue oxidative stress-related factors (malondialdehyde, glutathione peroxidase, total antioxidation capability, and superoxide dismutase) were assessed by colorimetry, myocardial pathology was observed by hematoxylin–eosin staining, and cardiomyocyte apoptosis was measured by triphosphate nick end-labeling staining, as well as the expression of miR-92b-3p and mitogen-activated protein kinase kinase kinase 2 (MAP3K2) in cardiac tissues were determined by reverse transcription quantitative polymerase chain reaction or western blot assay. The targeting relationship between miR-92b-3p and MAP3K2 was verified by bioinformatics, RNA immunoprecipitation, and luciferase reporter assays.miR-92b-3p was lowly expressed and MAP3K2 was highly expressed in myocardial I/R injury mice. Upregulation of miR-92b-3p improved hemodynamic indices, decreased serum levels of myocardial injury biomarkers, inhibited serum inflammatory response, alleviated cardiac tissue oxidative stress, relieved myocardial pathology, and reduced cardiomyocyte apoptosis during the myocardial I/R injury in mice. MAP3K2 was a direct target gene of miR-92b-3p.This research suggests that miR-92b-3p protects against myocardial I/R injury by inhibiting MAP3K2, which may provide novel candidates for treatment of myocardial I/R injury.
Keywords: microRNA-92b-3p; mitogen-activated protein kinase kinase kinase 2; myocardial ischemia-reperfusion injury; myocardial infarction; apoptosis